Neonatal malformations: organization of information flows in the S. Anna Hospital of Torino. (20th October 2021) - Bordino, V; Musso, A; Bert, F; Siliquini, R
Abstract: Background: Congenital malformations (CMs) represent a serious public health problem, both in terms of size (3% newborns/year) and severity of outcomes. The surveillance activity carried out by the Registers is an important tool for monitoring the frequency of events, to evaluate etiology, support research and public health actions. The aim is to evaluate the organization and the information network related to the diagnosis of malformation in the S. Anna presidium. Methods: the retrospective study analyzed all newborns with one or more CM and all cases of TOPFA (Termination of Pregnancy for Fetal Anomaly) for CMs in the period 01/2020 - 01/2021. A forward-looking pilot study was then set up to assess the impact on the quality of data collection through the introduction of a MC sheet. Results: 510 cases of CMs were found in live births, 180 in TOPFA for CMs and 4 in stillbirths. The duration of hospitalizations averaged 14.5 days (σ 36.56), with a median of 4 days. In the CMs group, an average maternal age of 33.40 years (σ 9.32), a median of 33 years and a mode of 33 years were calculated, in the TOPFA group an average maternal age of 34 years (σ 6.34), a median of 34 years and a mode of 32 years. In the live births group, 701 maternal diagnoses were detected, categorized and compared with the various national reports. The MC Sheet was compiled for 60 patients, 16 (4.30%) patients before the introduction of the sheet (01/2020 - 09/2020) and 44 (30.43%) after its introduction (10/2020 - 01/2021). Regarding the assessment of the proper use of ICD9CM an adequacy of 78% was observed in the first group vs one of 100% in the second. Conclusions: Our preliminary data assess the need for a Regional registry, for a comparison with the main national and regional sources available (also with a view to possible participation in the EUROCAT and ICBDSR registers) and for regional health planning. Key messages: The study underlines the need for a Regional Registry of congenital malformations. The clinical file is not always a complete source for analysing data on congenital malformations.